Prediction of the nonlinear behavior of laterally loaded piles in unsaturated soils. (December 2021) - Cheng, Xinting; Vanapalli, Sai K.
Abstract: This paper proposes an analytical method for estimating the load versus displacement curves for laterally loaded rigid piles in unsaturated soils taking account the influence of matric suction. The distribution of lateral soil resistance along the pile in this method considers three distinct states: (i) pre-tip yield state; (ii) post-tip yield state; and (iii) ultimate limiting state. The lateral earth pressure coefficient, K c required in this method is derived by extending the three-dimensional (3D) effect factor for drained loading. A numerical technique is also proposed which incorporates a user-defined subroutine (USDFLD) into ABAQUS for simulating the behavior of laterally loaded piles extending 3D finite element analysis taking account of nonlinear behavior of shear strength and modulus of elasticity with respect to matric suction. The proposed analytical method and numerical techniques were validated, respectively using the results of seven field studies and two laboratory tests published from the literature. In addition, close agreement was observed between the predictions of the proposed analytical method and numerical technique for a single pile example problem placed in a soil with varying groundwater table conditions. The summarized studies are promising for use in practice for the rational design of laterally loaded piles in unsaturated soils.